Developing English Digital Book for IX Grade Students of Junior High School - Iin Baroroh Ma'arif; Shintia Ira Claudia (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This research aims at developing a learning media based ICT called English Digital Book as supporting learning media for IX grade students of Junior High School. This English Digital book contains some materials and exercises which is appropriate to be learnt for junior high students. All materials in this learning media are based on syllabus of K13 curriculum. The research method used in this research is Research and Development. This development used ADDIE model which have five steps, those are; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. There are two expert vadidators in this research; those are material expert and media expert. The result of this research shows that from the media validation result got 95%, it was in “very good” category, whether from the material validation got 95% it was also in “very good” category. The students’ responses of field trial result was also in “very good” category. By having those result, this English digital book as learning media is feasible to be used for IX grade students of junior high school. Furthermore this research can be used as reference to other researcher in developing English learning media in different level of students.